Organizational Learning and Performance in Nepal’s Banking Sector - Parajuli, Suman Kamal (International Journal of Humanities, Education, and Social Sciences, 2025)
This study explores the relationship between organizational learning and organizational performance within Nepal’s commercial banking sector. It specifically examines four key dimensions of organizational learning—continuous learning, benchmarking, empowerment, and teamwork—and their influence on performance outcomes. A quantitative, cross-sectional research design was adopted, utilizing structured questionnaires administered to 155 entry-level employees from four major banks in Kathmandu. Data analysis was conducted using descriptive statistics, correlation, and regression techniques. The results indicate that empowerment exerts the most substantial positive impact on organizational performance, followed by teamwork and continuous learning. Conversely, benchmarking was found to have no significant direct effect on performance. These findings underscore the importance of cultivating a learning-oriented organizational culture that prioritizes employee empowerment and collaboration to drive improved performance outcomes in the banking sector.